2020
DOI: 10.18311/jnr/2020/24382
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, Antioxidant and Anticancer Activity of the Ethanol Extract of Pleurotus ostreatus

Abstract: The current study evaluates antimicrobial, antioxidant and anticancer activity of the ethanol extract of Pleurotus ostreatus. Chemical analysis showed the presence of alcohol, amides, alkanes, ether, phenol and sulphides. Most of the chemical constituents were found to be esters and carboxylic acid derivatives. The extract showed highest resistant against Bacillus cereus. P. ostreatus ethanol extract showed comparable antioxidant activity with ascorbic acid in both DPPH and FRAP method and also showed an IC 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…Their study showed anti-radical as well as considerable anti-diabetic activities [16]. Bindhu et al (2020) performed studies on ethanol extract of Pleurotus ostreatus for knowing its antimicrobial, antioxidant and anticancer activities [17]. Flavonoids, saponins, phenols, terpenoids, tannins, lipids, amino acids and alkaloids were present in ethanol extract of P. ostreatus as confirmed by qualitative phytochemical analysis [17].…”
Section: Journal Of Biotechnology and Bioprocessingmentioning
confidence: 92%
See 3 more Smart Citations
“…Their study showed anti-radical as well as considerable anti-diabetic activities [16]. Bindhu et al (2020) performed studies on ethanol extract of Pleurotus ostreatus for knowing its antimicrobial, antioxidant and anticancer activities [17]. Flavonoids, saponins, phenols, terpenoids, tannins, lipids, amino acids and alkaloids were present in ethanol extract of P. ostreatus as confirmed by qualitative phytochemical analysis [17].…”
Section: Journal Of Biotechnology and Bioprocessingmentioning
confidence: 92%
“…Extracts showed resistant against Bacillus cereus that may be beneficial in curing diarrheal related diseases. According to their study, ethanol extracts showed comparable antioxidant activity with ascorbic acid in both DPPH and FRAP method and IC50 of 39.29 μg/ml against HL60 cells [17].…”
Section: Journal Of Biotechnology and Bioprocessingmentioning
confidence: 95%
See 2 more Smart Citations